Woman’s Contribution in Contemporary Zakat: Mediating Role of Empowerment - Haifa Syukur; Aqifha Putri Ramadhani; Muhammad Nur Alam Muhajir; Novi Rahmadona; Dhea Amalia; Hilal; Muh. Afwan Ridha (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
There's been a lot of research on the role of women in household welfare. In contemporary times, one effective instrument in supporting women's economic role is productive zakat. The objective of this study is to uncover and understand the direct and indirect effects between digital skills and management effectiveness on household welfare, with empowerment acting as a mediating role. This study employs a quantitative method with data collection techniques using a questionnaire and snowball sampling. Data analysis utilizes the Partial Least Square Structural Equation Model (SEM PLS). The results of the study reveal that digital skills have no direct or indirect influence on household welfare. Meanwhile, digital skills influence empowerment. Furthermore, effective management has an influence on household welfare and empowerment. Conversely, effective management has no influence on household welfare through the mediation of empowerment. Meanwhile, empowerment has an influence on household welfare. This study is important to identify the factors that influence women's contribution to improving household welfare through the empowerment of zakat and productive waqf funds. The results of this study are expected to serve as a basis for formulating policy recommendations for the government, zakat institutions, and the broader community.